Comparative Analysis of Mechanized Farming Policies and Agriculture Green Development in Nigeria, Saudi Arabia and China: Towards Sustainable Agricultural Productivity in the 21st Century - Amuda, Yusuff Jelili; Al-Khateeb, Abdulqader (Journal of Posthumanism, 2025)
Sustainable agricultural productivity is an essential part of sustainable development goals (SDGs). Nigeria, China and Saudi Arabia have been striving to achieve sustainable agricultural productivity. However, less attention is given to comparative analysis concerning the utilization of mechanized farming in boosting agricultural productivity. This study therefore aims at exploring policies for adoption of mechanized farming practices in the aforementioned countries. The methodology employed in this study is content analysis of secondary data as integral part of quantitative research. The findings indicated that in the Nigerian context, mechanized harvesting and threshing, have been shown to significantly reduce food losses, increase yields, and positively impact socio-economic aspects. In China, agricultural mechanization plays a crucial role in reducing fertilizer input through increased agricultural mechanization investment, enhancing efficiency, and reducing pollution while in Saudi Arabia, mechanized farming policies have significantly evolved, driven by government initiatives aimed at fostering agricultural productivity and food security focusing on drought-resistant crops, water-efficient farming, and alternative protein. It is further shown that, comparatively, Nigeria China and Saudi Arabia differ in their agricultural policies, programmes, and structures, impacting their mechanization approaches. It is therefore suggested that policymakers should consider the demand-side factors influencing tractor adoption and the potential effects to drive comprehensive mechanization policies in order to boost agricultural productivity and encourage agripreneurs in the two countries.